Assessing tissue metabolism by phosphorous-31 magnetic resonance spectroscopy and imaging: a methodology review - Liu, Yuchi; Gu, Yuning; Yu, Xin (Quantitative Imaging in Medicine and Surgery, 2017)
Abstract: Many human diseases are caused by an imbalance between energy production and demand. Magnetic resonance spectroscopy (MRS) and magnetic resonance imaging (MRI) provide the unique opportunity for in vivo assessment of several fundamental events in tissue metabolism without the use of ionizing radiation. Of particular interest, phosphate metabolites that are involved in ATP generation and utilization can be quantified noninvasively by phosphorous-31 (31P) MRS/MRI. Furthermore, 31P magnetization transfer (MT) techniques allow in vivo measurement of metabolic fluxes via creatine kinase (CK) and ATP synthase. However, a major impediment for the clinical applications of 31P-MRS/MRI is the prohibitively long acquisition time and/or the low spatial resolution that are necessary to achieve adequate signal-to-noise ratio. In this review, current 31P-MRS/MRI techniques used in basic science and clinical research are presented. Recent advances in the development of fast 31P-MRS/MRI methods are also discussed.